Gentamicin blockade of slow Ca++ channels in atrial myocardium of guinea pigs. - Adams, H R (1978)
Cardiac dysfunction is occasionally detected in patients undergoing treatment with amino-glycoside antibiotics, however, the mechanism responsible for the negative inotropic effect of these agents has not been identified. In the present investigation electrically driven left atria of guinea pigs were used to study the effects of gentamicin on calcium ion (Ca++)-dependent contractile events in heart muscle isolated from in vivo influences. When atria were first inactivated by excess potassium ion (K+; 22mM) and contractions were then restored by isoproterenol (an experimental model that accentuates the contractile dependence of myocardial fibers on influx of Ca++ through specific "slow channels" of the sarcolemma), the cardiac depressant activity of gentamicin (0.1 mM) was profoundly augmented. Conversely, the negative inotropic effect of tetrodotoxin (23.5 micron) was abolished by the same experimental conditions. Also, gentamicin (1 mM) and La+++ (0.5 mM) markedly decreased the positive inotropic response to increased frequency of stimulation; whereas, D600 (1.05 micron) converted the positive frequency-force relationship to a negative relationship. Present data indicate a direct cardiac depressant action of gentamicin, and suggest that this antibiotic adversely affects either the transport system responsible for Ca++ movement through slow channels of the sarcolemma, the availability of Ca++ for translocation to these sites, or both.